Historic challenges of inclusion: Institutional features of two new federal universities in Brazil - Eduardo Santos; Manuel Tavares (Arizona State University, 2016)
This paper is a reflection on the new university models that emerged in Brazil from government of Luis Inácio Lula da Silva (2002-2010), continued from the former government of Dilma Roussef. In our view, they represent a "transgression" in relation to the classic models of the university and a national response against the hegemonic lines of power (conceptual and political) of a wider process of reconfiguration of higher education in the contemporary world. We take as case studies for this debate the federal universities of Fronteira Sul (UFFS), based in Chapecó, Santa Catarina, and Sul da Bahia (UFSB), based in Itabuna, Bahia, because they are institutions that assume commitments with the ecology of knowledge (Santos, 2004; Benincá, 2011) and with the omnilateral cognitive democracy (Romão, 2013), which places the university at the service of historically oppressed populations and promotes the inclusion of other territories, cultures and epistemologies. In their founding documents both institutions claim the condition of radically democratic and strongly inclusive universities, as well as proposing a focus on regional integration. We defend the claim that such models are close to a popular perspective of higher education, from the point of view of its institutional and curricular matrices or their inclusion policies. This text is guided by the analysis of data collected with research professors of the project "Monitoring the Popular University in Brazil," developed by the Program of Graduate Studies in Education, University Nove de Julho (PPGE-Uninove).